Adapting a Participatory and Ecosystem-Based Assessment Impacted by the Pandemic: Lessons Learned With Farmers in Tajikistan - Spies, Michael; Schick, Axel; Karomatov, Sharofiddin; Bakokhoja, Bobozoda; Zikriyokhon, Khaidarov; Jobirov, Shonazar; Bloch, Ralf; Ibisch, Pierre L. (Frontiers in Sustainable Food Systems, 2021)
The paper presents a systemic and participatory assessment approach and scrutinizes how methodological changes necessitated during the Covid-19 pandemic implicated the process and its outcomes. The approach was applied in rural Tajikistan to evaluate changes effected by a development project that promoted the enhancement of biodiversity and ecosystem services in agrarian landscapes. The central building block of the assessment consisted of participatory workshops in 2018 and 2020 with farmers and other stakeholders to develop a systemic knowledge map and to evaluate the promoted strategies based on local expertise. The methodological basis was MARISCO (adaptive MAnagement of vulnerability and RISk at COnservation sites), a holistic and participatory approach to ecosystem-based assessment and management that requires well-trained facilitators. While the activities in 2018 could be implemented as planned, major changes in the work plan were necessary in 2020 due to severe travel restrictions and social distancing rules. Conducting virtual workshops was not possible, as it would have excluded key stakeholders from the process. Instead of conducting a comprehensive assessment workshop guided by two German MARISCO facilitators as originally planned, a series of short and small workshops could be realized. These workshops were facilitated by Tajik scientists after receiving virtual training from their German colleagues. Although it was possible to bring the assessment to a satisfactory conclusion, the methodological changes revealed significant drawbacks. Radical simplifications of the methods were necessary that led to reduced depth of the assessment and missed learning opportunities for participants. Limited experience in workshop guidance by the new facilitators posed challenges to the participatory process and the quality of its outcomes. While the adapted method created training effects that would otherwise have been missed, it also put additional pressure on the capacities of local partners. Our experience during the pandemic offers valuable lessons learned for future applications of systemic-participatory approaches. Whereas, a complete shift to remote applications is problematic, there is a need to put greater emphasis on capacitating local partners. Methodological trade-offs are necessary for partially remote working processes, but principles of participation and systemic thinking should not be compromised.